Flexiseguridad, derecho al trabajo y estabilidad laboral - Blancas Bustamante, Carlos (2012)
Flexisecurity, right to work and labor stability This article deals with one of the most recent and innovative proposals of related flexibilization, basically, to the extinction of labor relation and that areknown as «flexisecurity» or «flexicurity». For this, the author comments the model of Denmark – country in which it’s originated «flexisecurity» – emphasizing the configuration of a «golden triangle», composed of: i) flexibility in the labor relation, aimed at facilitating the dismissal ii) a generous system of unemployment benefits, funded primarily by the State and iii) a new policy of «activation» of the labor market, which seeks to keep large sectors of the population permanently trained to meet new labor challenges. The author emphasizes the difference between our country and Denmark, since it is a Welfare State with a high level of social protection funded by a fiscal pressure and high tax rates. Finally, the article notes that for the study of «flexisecurity» it shouldn’t ignore the legal framework derived from workers’ fundamental rights established in the Constitution and international treaties which imply: right to work, dignity and citizenship of the worker and Trade Union Freedom and Collective Rights